The Use Of Learn English With Jessica Youtube Channel On Students’ Listening Skills at SMPN 3 TOMOHON - Lengkey, Febrika; Liando, Nihta V. F; Ismail (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
This study investigates the use of LEWJ (Learn English with Jessica) YouTube channel on students’ listening skills of eighth-grade students at SMPN 3 Tomohon during the 2024/2025 academic year. The focus is on students’ ability to identify main ideas, understand specific information, and recognize explicit meanings. Using a quantitative method with a pre-experimental one-group pretest-posttest design, the research involved 32 students from class 8A. Data were collected through a 20 item multiple-choice listening test and analyzed using SPSS version 30. The descriptive results showed a notable increase in the average score from 33.75 in the pretest to 63.12 in the posttest. The normality test confirmed the data were normally distributed, while the paired sample t-test showed a highly significant difference (p < 0.001) between pretest and posttest scores. These findings clearly indicate that the LEWJ YouTube channel effectively improved students’ listening skills. The statistical evidence supports the success of this study, as the improvement was not due to chance but confirmed through valid data analysis. Therefore, the integration of structured audiovisual media like LEWJ YouTube content can be considered an effective method for enhancing junior high school students’ listening comprehension in English.